Development of Computer State Identification Method Based on Boosting Ensemble - Chelak, Viktor; Gavrylenko, Svitlana (My University, 2021)
This work is about developing a modification of boosting method by using a special preprocessing procedure to improve the accuracy of computer system state identification. The aim of the research is to develop method for detection computer threats, malware, etc. Experimental research have confirmed the effectiveness of the proposed method, which makes it possible to recommend it for practical use in order to improve the accuracy of identifying the state of the computer system. Prospects for further research may be to develop an ensemble of fuzzy decision trees based on the proposed method, optimizing their software implementation.
Keywords: computer system state identification; data processing; decision tree boosting ensembles